A review on structural health monitoring of railroad track structures using fiber optic sensors. (2020) - Sasi, Deepika; Philip, Shimol; David, Robin; Swathi, J.
Abstract: Railroads are an important part of India's public transport facilities. Railway services and networks have been emanated as a remarkably resourceful mode of transport to fulfill the continuing requisition for passenger transport and cargo services. The utilization of such systems under extreme working and loading environment makes it highly vulnerable to deterioration and failure. Hence, the Structural Health Monitoring (SHM) of railroad track structures is quite crucial for safeguarding the rail structures, in order to avoid catastrophic mishaps and also considerably decrease the maintenance cost. Today, in structural health monitoring applications, Fiber Optic Sensor (FOS) has indeed found widespread use on account of its intrinsic characteristic advantages, viz reduced size, resistance to electromagnetic interference (EMI) lightweight, corrosion and embedding capacity. FOS enables early diagnosis and characterization of damage, leading to real-time measurement, timely remediation and prevention of mechanical failures. Thus, in the existing scenario, FOS has been substantiated as a prominent tool for detailed examination of railroad track structures. The present review encapsulates the fundamental concepts of numerous fiber optic sensors. Their onsite applications in the analysis of railroad track structures are also discussed. Specifically, the emphasis will be on FOS implementation in the analysis of rails, concrete ties/sleepers and ballast, rail components, railway subgrade, railway tunnels and bridges, and structures prone to landslides as well. The simplicity, immunity to corrosion and EMI, dissociated long-range sensing; non-intrusive sensing and signal vulnerability of FOS makes them a prevalent and beneficial approach to structural health monitoring.